PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. CILACAP KENDARI - Pebrianti, Elmi; Aliddin, Laode Asfahyadin; Masri, Muhamad; Hasan, Rachmat Riyaldi; Sabri, Sabri; Hakim, Adnan (Jurnal Manajemen dan Kewirausahaan, 2024)
This study aims: (1) To determine simultaneously the effect of compensation and work motivation on theperformance of employees of PT. Cilacap Kendari (2) To determine the effect of compensation on the performance of employees of PT. CilacapKendari. (3) To determine the effect of work motivation on the performance of employees of PT. Cilacap Kendari. The total population in this study is all employees as many as 45 people who are also used as research samples usingpurposivesamplingtechnique.Thisstudyusesmultiplelinearregressionanalysis. The results showed that: (1) Compensation and motivation have a simultaneous effect on the performance of employees at PT. Cilacap Kendari. (2) Compensation has a positive and significant effect on the performance of employeesof PT. Cilacap Kendari (3) Work motivation has a positive and significant effect on the performance of employees of PT. Cilacap Kendari